Maternal Sedentary Behavior and Physical Activity across Pregnancy and Early Childhood Motor Development - Melissa A. Jones; Kara M. Whitaker; Sharon E. Taverno Ross; Kelliann Davis; Klaus Libertus; Bethany Barone Gibbs (MDPI AG, 2021)
Early childhood motor development is an important indicator of short- and long-term health. In utero exposures impact offspring health across the lifespan; however, whether maternal activity during pregnancy may impact early childhood motor development remains unknown. This prospective cohort study measured the motor development skills of n = 70 children born to mothers from a previously conducted cohort study which objectively measured activity profile, (sedentary behavior (SED) and moderate-to-vigorous intensity physical activity (MVPA), across pregnancy. Mothers reported the motor development of their child using the Early Motor Questionnaire (EMQ). Linear regression models examined associations between maternal activity profile and EMQ scores. Maternal SED and MVPA were analyzed in two ways: trimester-specific and across pregnancy using trajectory groups. Children were 12-30 months of age, majority white (82%), and 52% male. Maternal SED during pregnancy was not associated with any EMQ domains (gross motor, fine motor, and perception action). Higher maternal MVPA, across pregnancy by trajectory group and in the first and second trimesters, was significantly associated with moderate-sized effects of more advanced fine motor and perception action scores. Higher MVPA in early pregnancy appears to be related to more advanced early childhood motor development. Therefore, maternal MVPA may be a modifiable behavior by which short- and long-term offspring health may be impacted.